The Effect of Black Seed Oil as Adjuvant Therapy on Nuclear Factor Erythroid 2-Related Factor 2 Levels in Patients with Metabolic Syndrome Risk: Effect of Black Seed Oil as Adjuvant Therapy on Nuclear Factor Erythroid 2-Related Factor 2 - A Hi, Wahid Rahmat; Endang, Darmawan (Iranian Journal of Pharmaceutical Sciences, 2020)
Nuclear factor erythroid 2-related factor 2 (Nrf2) is one of the transcription factors involved in providing endogenous antioxidants. Black seed oil (BSO), suspected have antioxidant effects that can be used to modulate the expression and levels of Nrf2. The study aims to determine the effect of BSO as adjuvant therapy on levels of Nrf2 to the patients with metabolic syndrome risk.The research used analytical observational with cohort design. Samples study consisted of 62 patients at risk with metabolic syndrome risk at Jetis I Public Health Center, Bantul District, from September to December 2016. Eligible subjects were divided into two groups, (1) BSO group, patients get BSO with a dose of 3 mL/day and standard therapy for 20 days. (2) Control group, patients got placebo and standard therapy during the intervention for 20 days. Levels of Nrf2 were estimates using enzyme-linked immunosorbent assay (ELISA) method. The mean values ± SD between groups were tested with independent t-test with significance of p=<0.05 (95%). The results showed that Nrf2 in group 1 was 0,866 ± 0,11 ng/ml and the group 2 was 0,864 ± 0,15 ng/mL (p=0,94). There were no significant difference in the both groups (p>0.05).In conclusion, adjuvant therapy of BSO doses 3 mL/day for 20 days could not increase levels of Nrf2 in the patients with metabolic syndrome risk based on type treatment and demographic characteristic at Jetis I Public Health Center, Bantul District.